Clean & Sustainable process for Zeolite Synthesis: Effect of Acidic Pretreatment and Double Fusion on the Characteristics. (2017) - Joshi, Parag
Abstract: The application of Coal fly ash (CFA) to synthesize a catalyst finds a noble way to utilize this abundant waste material as their management has been a concern with various approaches for its beneficial uses. Various research and development activities were being conducted to identify and develop the synthesis of catalyst (Zeolite) from coal fly ash (CFA). In this research, CFA was used to synthesize CFA a type of Zeolite catalyst being commercially used, with the help of acid pre-treatment and base post treatment which is subsequently followed by hydrothermal treatment. The use of mixing CFA with acids and bases advances the physicochemical properties of the catalysts such as pore size, pore volume, stability, crystal structure etc. and hence the activity of the Zeolite. The physicochemical properties of Zeolite were evaluated by XRD, XRF and SEM analysis. XRD was used to determine the crystal structure of the Zeolite crystals, SEM was used to determine the morphological structure and texture properties and XRF was used for routine, relatively non-destructive chemical analysis of the Zeolite. The fusion temperature and drying temperature had significant effect in this process of Zeolite preparation. This work also suggests that the performance of the Zeolite obtained from the optimal conditions is more efficient than that of the commercial catalysts. Thus, the aim of this work is to valorize the CFA waste for the preparation of the Zeolite.